Serotonin modulates outward potassium currents in mouse olfactory receptor neurons - Gao, S; Guo, X; Liu, T; Liu, J; Chen, W; Xia, Q; Chen, Y; Tang, Y (Physiological research, 2013)
Monoaminergic neurotransmitter 5-hydroxytryptamine (5-HT), also known as serotonin, plays important roles in modulating the function of the olfactory system. However, thus far, the knowledge about 5-HT and its receptors in olfactory receptor neurons (ORNs) and their physiological role have not been fully characterized. In the present study, reverse transcription-polymerase chain reaction (RT-PCR) analysis revealed the presence of 5-HT(1A) and 5-HT(1B) receptor subtypes in mouse olfactory epithelium at the mRNA level. With subtype selective antibodies and standard immunohistochemical techniques, both receptor subtypes were found to be positively labeled. To further elucidate the molecular mechanisms of 5-HT act on the peripheral olfactory transduction, the whole-cell patch clamp techniques were used on freshly isolated ORNs. We found that 5-HT decreased the magnitude of outward K(+) current in a dose-dependent manner and these inhibitory effects were markedly attenuated by the 5-HT(1A) receptor blocker WAY-100635 and the 5-HT(1B) receptor antagonist GR55562. These data suggested that 5-HT may play a role in the modulation of peripheral olfactory signals by regulating outward potassium currents, both 5-HT(1A) and 5-HT(1B) receptors were involved in this regulation.
Keywords: draslíkové kanály; Animals; Receptor, Serotonin, 5-HT1A; membránové potenciály; receptor serotoninový 5-HT1B; Serotonin; receptor serotoninový 5-HT1A; serotonin; Mice; signální transdukce; messenger RNA; myši; Signal Transduction; čichové buňky; RNA, Messenger; antagonisté serotoninových receptorů 5-HT1; Olfactory Receptor Neurons; Serotonin 5-HT1 Receptor Antagonists; Potassium Channels; Receptor, Serotonin, 5-HT1B; zvířata; Membrane Potentials